Stimulation of Cultured H9 Human Embryonic Stem Cells with Thyroid Stimulating Hormone Does Not Lead to Formation of Thyroid-Like Cells. (11th March 2012) - Onyshchenko, Mykola I.; Panyutin, Igor G.; Panyutin, Irina V.; Neumann, Ronald D.
Abstract : The sodium-iodine symporter (NIS) is expressed on the cell membrane of many thyroid cancer cells, and is responsible for the radioactive iodine accumulation. However, treatment of anaplastic thyroid cancer is ineffective due to the low expression of NIS on cell membranes of these tumor cells. Human embryonic stem cells (ESCs) provide a potential vehicle to study the mechanisms of NIS expression regulation during differentiation. Human ESCs were maintained on feeder-independent culture conditions. RT-qPCR and immunocytochemistry were used to study differentiation marker expression, 125 I uptake to study NIS function. We designed a two-step protocol for human ESC differentiation into thyroid-like cells, as was previously done for mouse embryonic stem cells. First, we obtained definitive endoderm from human ESCs. Second, we directed differentiation of definitive endoderm cells into thyroid-like cells using various factors, with thyroid stimulating hormone (TSH) as the main differentiating factor. Expression of pluripotency, endoderm and thyroid markers and 125 I uptake were monitored throughout the differentiation steps. These approaches did not result in efficient induction of thyroid-like cells. We conclude that differentiation of human ESCs into thyroid cells cannot be induced by TSH media supplementation alone and most likely involves complicated developmental patterns that are yet to be understood.